Analisis Struktural Dan Nilai Kearifan Lokal Cerita Rakyat “Pelleng Peneppuh Babah” Dari Etnis S Pakpak Dan “Berhala Fosi Di Selatan” Dari Etnis Nias (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This study aims to examine the structural and local wisdom values found in the folklore of the some ethnic group in North Sumatra, like as Pakpak and Nias. The method used in this study uses a library approach. The sources of data used in this research are journals, books, and internet sites related to the topics that have been selected. The results of this study are that there are many local wisdom values in Pakpak ethnic folklore. This is reflected in the oral/regional literary tradition in the form of folklore from the Pakkpak ethnic in North Sumatra, structural values and local wisdom values that have been analyzed can be used as material teaching, namely literature learning material due to the suitability between existing stories and existing material with the 2013 Curriculum for class X SMA.